PS-112 Pharmaceutical analysis of assistance on reconciliation of paediatric medicines. (24th March 2015) - Raich Montiu, L; Rudi Sola, N; De Castro Julve, M; Silva Riadigos, G; Gorgas Torner, MQ
Abstract : Background: Medicines reconciliation is one of the strategies used to minimise drug-related adverse effects. Purpose: To detect and analyse potential medicines errors in a paediatric population at the time of admission. Material and methods: From May to July 2013 the daily admissions of paediatric patients were reviewed. Only patients who had already been prescribed medicines were selected. We reviewed patients who had previously received treatment appropriate to their current condition as well as drugs prescribed because of an acute illness. Some prescriptions were verified by clinical interviews. Differences were categorised into no discrepancies or discrepancies and these last into justified or unjustified. The unjustified were defined as drug omissions or drug interactions detected and were communicated to paediatricians. Data collection was classified by age, sex, and medicine (dose and route of administration). The time was noted when discrepancies were detected and the gravity measured in a scale from 1 to 3, representing the impact to the patient. An exclusion criterion was hospitalisation for less than 24 h. Results: 30 patients were analysed, 18 boys and 12 girls, mean age 8.6 years. A total of 47 medical prescriptions were reviewed. Clinical interviews were held with 11 patients. Of 47 prescriptions, 11 (23.4%) were categorised as no discrepancies, 17 (36.1%) as justified discrepancies and 19 (40.4%) as unjustified discrepancies. Of these 19 unjustified discrepancies, 18 resulted from drug omissions and 1 drug interaction was detected. 11 (57%) of unjustified discrepancies were communicated to the paediatricians and a change in the medical prescription was requested. Antimicrobials and inhaled treatments were the most common drugs omitted. Almost all of them were detected on the first day. The mean gravity was 2.4. Conclusion: From a total of 47 medical prescriptions, 11 (24.3%) potential medicines errors were avoided. We believe pharmaceutical care focused on medicines reconciliation is an important tool to optimise paediatric medical prescriptions. References and/or acknowledgements: Multidisciplinary team No conflict of interest.